Aktivitas dan Hasil Belajar Matematika Siswa Melalui Model Cooperative Learning Tipe Pair Check - Tuti Widya; Aniswita Aniswita; Intan Sari (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
overcome this problem is to use the Pair Check type Cooperative Learning model in learning mathematics. The purpose of this study was to find out how the activities of class VIII students of SMPN 4 Lareh Sago Halaban in the 2019/2020 academic year using the Cooperative Learning model of the Pair Check type and to find out how the mathematics learning outcomes of students who used the Cooperative Learning model of the Pair Check type were better than conventional learning. in class VIII of SMPN 4 Lareh Sago Halaban for the 2019/2020 academic year. This type of research is a pre-experimental research design, namely The Static Group Comparison: Randomized Control Group Only Design. The population in this study were all eighth grade students of SMPN 4 Lareh Sago Halaban for the 2019/2020 school year. Sampling was done randomly, obtained class VIII 1 as the experimental class and class VIII 2 as the control class. Activity data was obtained from observation sheets and learning outcomes were obtained from students' mathematics learning test results. Based on the analysis of student activity observations, overall student activities with the Pair Check type Cooperative Learning model are classified as active with an average of 70.19%. From the hypothesis test, it was obtained that tcount = 2.11 and ttable = 1.68, because tcount > ttable, H0 was rejected and H1 was accepted. And from the calculation of SPSS16 obtained a significant value of 0.041, = 0.05 and a significant value <α so that H0 is rejected. It can be concluded that students' mathematics learning outcomes with the Pair Check type of Cooperative Learning Model are better than conventional learning in class VIII of SMPN 4 Lareh Sago Halaban for the 2019/2020 school year